THE EMPOWERMENT OF COMMUNITY BY C-KIP TO IMPROVE THE SLUMS - Dewi Septanti (Journal of Architecture&ENVIRONMENT, 2016)
Surabaya has long term experience in conducting slum upgrading program. Started from colonial era which known as KIP Verbetering until the most recent one, called KIP program (Comprehensive – KIP which was funding by Indonesian government). The last program tried to involve community participation by using Three Empowerment (Tri Daya) sustainability scheme : Environmental, Social, and Economic. People can participate as the decision maker, implementer or supervisor in this program. Based on this scheme, the C-KIP model spread its successes through the country and across the developing world. The combination between research and design methods, where the research strategy is using qualitative strategy is the method which used in this study. The data collection techniques are using documentation observation and stakeholders interview (community, facilitator and government). By empowering community's capacity, government had many advantages such as getting people to be  more attentive to the program, reaching maximum result with a small budget, the implementation and monitoring program can be done by community, involving more people in getting benefits from the program, making room for people to  participate and be responsible to take care of the program, etc.